2016
DOI: 10.1016/j.jpsychores.2016.03.165
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin and mineral status in chronic fatigue syndrome and fibromyalgia syndrome: a systematic review and meta-analysis

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…Our data regarding the high prevalence rate of VDD among FMS patients is in agreement with previous studies [1,[10][11][12][13][14][15]. In an earlier study, Abokrysha, et al examined the vitamin D levels in 30 FMS Saudi female patients, and the data showed a mean concentration of 4.76 ± 1.46 ng/mL indicating a high prevalence of severe VDD among this population [10].…”
Section: Discussionsupporting
confidence: 92%
“…Our data regarding the high prevalence rate of VDD among FMS patients is in agreement with previous studies [1,[10][11][12][13][14][15]. In an earlier study, Abokrysha, et al examined the vitamin D levels in 30 FMS Saudi female patients, and the data showed a mean concentration of 4.76 ± 1.46 ng/mL indicating a high prevalence of severe VDD among this population [10].…”
Section: Discussionsupporting
confidence: 92%
“…Reduced caloric intake and consumption of carbohydrates, proteins, lipids, vitamins A, E, K, folate, selenium, and zinc have been reported. Additionally, a positive correlation between protein intake and pain threshold, and an association between vitamin E and quality of life, has been documented [16,81,82].…”
Section: Current Treatment Of Fibromyalgiamentioning
confidence: 98%
“…However, the idea that vitamins and nutritional supplements directly correlate to the pathophysiology of the disease is one that is disputed. In fact, some research has found no statistical correlation between the use of supplementation and the effectiveness for patients [81]. One study looked to examine the correlation between monosodium glutamate (MSG) intake and the symptoms of FM; patients that discontinued the consumption of MSG tended to have similar levels of pain as those in the control group.…”
Section: The Role Of Nutrient Supplementation For Pain Management In Patients With Fibromyalgiamentioning
confidence: 99%
“…Cela s'explique possiblement par la difficulté d'établir un diagnostic formel, l'absence de tests diagnostiques validés [37][38][39], et l'absence de traitement [40][41][42][43][44][45]. Le délai diagnostic moyen de 7…”
Section: Résultatsunclassified